Long-term success of inlay and onlay procedures in dental repairs - Alakkad, Tarik M. A.; Alshammari, Naif M.; Alhertani, Safaa M. R.; Rizq, Ibrahim M.; Musawi, Khadija A.; Alalwan, Abeer A.; Alammari, Khalid A.; Alhumaidan, Sara A.; Asiri, Yahya N.; Alkurbi, Asma A.; Alshammari, Reem R. (International Journal Of Community Medicine And Public Health, 2024)
Inlays and onlays are vital restorative techniques in dentistry, offering a conservative alternative to full crowns while preserving more of the natural tooth structure. These restorations, typically made from ceramic or composite resin materials, provide both aesthetic and functional benefits and are increasingly favored for their durability and longevity. In contrast to direct restorations, inlays and onlays are fabricated outside the mouth, allowing for greater precision and a more customized fit. The clinical success of these restorations largely depends on factors such as material choice, bonding technique, and patient-related variables like oral hygiene and habits. Ceramic materials are particularly noted for their resistance to wear and their ability to closely mimic the natural appearance of teeth, making them an attractive option for both patients and clinicians. Composite resins, while slightly less durable, offer a cost-effective alternative with satisfactory long-term results. Proper bonding techniques and high-quality materials are essential for ensuring the durability of inlays and onlays, with many restorations lasting over a decade. Patient-related factors also play a significant role in the success of inlays and onlays. Effective oral hygiene, regular dental check-ups, and the avoidance of habits like bruxism are essential for maintaining the integrity of these restorations over time. Despite the challenges and technical demands associated with their placement, inlays and onlays are highly successful when properly executed, offering patients a durable, aesthetically pleasing solution for dental repairs. The discussion of this review focuses on the critical elements that influence the long-term success of inlays and onlays, including material selection, clinical technique, and patient management, highlighting their effectiveness as a restorative option in modern dentistry.